Efficiency Marketing of Smoked Fish in Lingga Regency - Tetty, Tetty; Haidawati, Haidawati; Khairunnisa, Khairunnisa; Wahyudin, Wahyudin; Hafsar, Khairul; Ilhamdy, Aidil Fadli; Muzammil, Wahyu; Nurhasanah, Septia (Agrikan: Jurnal Agribisnis Perikanan, 2021)
Utilization of fishery in Lingga Regency is fresh fish  and processed into smoked fish as we known ikan  salai. The smoked Fish raw material is  Fringescale sardinella (Sardinella Fimbriata).  Specifically, this research is to know : (1) the marketing distribution channel of  smoked fish in Lingga Regency, (2) the marketing efficiency of smoked fish in Lingga Regency. The research was conducted in September - December 2021. In the Lanjut, Berindat, Persing, and sedamai village, Singkep Pesisir District, Lingga Regency. The results of the study show is  there are 2 marketing channels . Marketing channel 1,   the margin amount is Rp. Rp28,462,   fishery share is 34,62% and marketing  efficiency is 0,57%.   Marketing channel 2,  the margin amount is Rp 13,750, fishery share  is 75, 42%, and marketing efficiency is 0,74%. The value of marketing efficiency is 0.57% and 0.74%. The marketing channels of smoked fish  in this area is efficient.